Gest??o de imagem de celebridades esportivas: o caso da constru????o da imagem de Anderson Silva - Salles, Carlos Affonso Sartore (2015)
The purpose of this study is to indicate ways for the diagnosis image of athletes and sports celebrities. It was realized a case study using the Brazilian athlete and MMA fighter Anderson Silva, taking advantage of your image notoriety inside and outside of sports, the fact of he participates in an emerging sport that generates controversial opinions, as well as recent events in his career in 2013 and 2014, which generated adverse opinions, doubts and questions about hisattitudesin the competition. To achieve the purpose, an interviews guide that addressed the issues of image management, crisis management and sports celebrities, being composed mainly by M??todo de Configura????o de Imagem (MCI), which assisted in the disclosure of attributes that configured the image athlete object of the study. As a result, it is understood that the instrument can be used as a tool for managing the image sports personalities.